Peri-Operative Anaphylaxis—An Investigational Challenge - Misbah, Siraj A.; Krishna, Mamidipudi Thirumala (Frontiers in Immunology, 2019)
Patients with suspected peri-operative anaphylaxis (POP) require thorough investigation to identify underlying trigger(s) and enable safe anaesthesia for subsequent surgery. The changing epidemiology of POP has been striking. Previous estimates of the incidence of POP have ranged between 1:6,000 to 1:20,000 anaesthetics, but more recent data from France and the United Kingdom suggest an estimated incidence of 1:10,000. Other important changes include a change in the hierarchy of well-recognised triggers, with antibiotics (beta-lactams) supplanting neuromuscular blockers (NMB) as the leading cause of POP. The emergence of chlorhexidine, patent blue dye and teicoplanin as important triggers have also been noteworthy findings. The mainstay of investigation revolves around critical analysis of the time-line of events leading up to anaphylaxis coupled with judicious skin testing. Skin tests have limitations with respect to unknown predictive values for most drugs/agents and therefore, knowledge of background positivity in healthy controls, test characteristics of individual drugs and the use of non-irritant concentrations is essential to avoid both false-positive and false-negative results. Specific IgE assays for individual drugs are available only for a limited number of agents and are not a substitute for skin testing. Acute serum total tryptase has a high specificity and positive predictive value in IgE-mediated POP anaphylaxis but is limited by its moderate sensitivity and negative predictive value. Planning for safe anaesthesia in this group of patients is particularly challenging and consequently anaesthetists need to be alert to the possibility of repeat episodes of anaphylaxis. Because of the limitations of current investigations for POP, collecting systematic data on the outcome of repeat anaesthesia is valuable in validating current investigatory approaches. This paper reviews the changing epidemiology of POP with reference to the main triggers, and the investigation and outcome of subsequent anaesthesia.